Political animal : Gore Vidal on power - Neilson, Heather (Investigating Power., 2014)
The late Gore Vidal occupied a unique position within American letters. Born into a political family, he ran for office several times, but was consistently critical of his nation's political system and its leaders. A prolific writer in several genres, Vidal was also widely known - particularly in the US - on the basis of his frequent appearances in the various electronic media. This ground-breaking work examines the centrality of the theme of power throughout his writings. Political Animal: Gore Vidal on Power focuses primarily, although not exclusively, on Vidal's historical fiction. In his n.